Effect of Transformational Leadership, Motivation, and Affective Commitment on Organizational Citizenship Behavior (OCB) - Ifta Firdausa Nuzula; Intan Tamara Febrinzky; Sekar Shabrina Ramadhany (The Indonesian Institute of Science and Technology Research, 2022)
This study aims to see the effect of Transformational Leadership on Organizational Citizenship Behavior (OCB), with Motivation, Affective Commitment as the mediating variable. The method used in this research is quantitative by distributing questionnaires. The technique of taking samples is purposive sampling. The sample used is BUMN employees for at least one year. The number of respondents obtained was 120 respondents. Software applications performed with Smart PLS. The results of the study indicate that by path analysis, the variable of Transformational Leadership towards OCB with the mediator variables of Motivation and Commitment was significant because the p-value level is below 0.05.